A future for facility management. Issue 2 (3rd April 2017) - Atkin, Brian; Bildsten, Louise
Abstract : Purpose: This paper aims to discuss the current debates in facility management to understand where the research community is working and where the facility management sector and discipline might be heading. Design/methodology/approach: A review of research outputs has been undertaken to identify research themes. The discussion is based on developments that are already shaping how one should view facility management and outlines a possible future based on a number of strategically important questions and their likely answers. Findings: There is a broad landscape of research themes; yet, a significant portion of the most-cited journal papers were published more than 10-15 years ago. Current debates are focused mostly on operational improvement; few are directed at more strategic objectives. Those in the informal media are concerned with more speculative themes, particularly the internet of things (IoT) and artificial intelligence (AI), which are indicative of disruptive technology. These themes are debated mostly by practitioners. Originality/value: Many views are expressed in this editorial – some are controversial whilst others should be regarded as matters of fact. The underlying aim is to stimulate debate and action among readers about what appears to be a dilemma for the facility management sector and discipline. Does it continue along the same trajectory or should it be bold and strike out in new directions and meet the challenges presented by disruptive innovations, notably the IoT and AI? Hard choices await and not all decisions will lead to preferred outcomes.